Pemeriksaan Kesehatan Warga Suku Baduy Dalam dan Baduy Luar dalam Rangka Social Empowerment 3.0 BEM KMF Kedokteran UNJANI - Saptarani, Yanna Dwi; Irviana, Fitriyati (Prisani Cendekia, 2026)
The Baduy Luar and Baduy Dalam communities in Lebak Regency, Banten Province, represent indigenous groups with limited access to routine health examinations and modern medical services. This community service program aimed to improve health awareness and provide basic health examinations for the Baduy community through the Social Empowerment 3.0 initiative organized by BEM KMF Faculty of Medicine, Universitas Jenderal Achmad Yani (UNJANI). The program employed a promotive and preventive, community-based approach that respected local cultural values and involved collaboration with traditional leaders and community representatives. Activities included basic health examinations, identification of common health complaints, and simple health education tailored to the community’s context. The results of the program indicated that many participants had never undergone routine health check-ups prior to the activity. Basic health examinations enabled early detection of minor to moderate health complaints, while health education activities increased community awareness regarding personal hygiene, early recognition of health problems, and the importance of maintaining overall health. Overall, this community service activity demonstrated that culturally sensitive, community-based health interventions can effectively enhance health awareness and support early detection of health problems among indigenous populations.